Systemic risk in the angolan interbank payment system : a network approach - Borges, Maria Rosa (2022)
In this work, we analyse the topology of the network of interbank payment flows settled via the real-time gross settlement system (RTGS) of the Angolan payment system (APS) during the fourth quarter of 2016, with the aim of discussing the APS resilience to systemic risk, focusing on its vulnerability in case of failures in the settlement of any bank payments. We conclude that (i) the Angolan RTGS payment network is sparse, characterized by low connectivity, (ii) it is a scale-free network with five banks with high connectivity, representing the main origin and destination of the settled transactions and concentrating about 47% of the total volume and amount of pay ments settled, which adds to contagion risk. However (iii) the systemic risk arising from the removal of a single participant from the network is low, since the largest bank in the system, with the greatest transacted volume and amount, accounts only for about 11% of the total transacted amounts. In addition, (iv) the adequate risk-mitigating operational processes of each of the RTGS subsystems safeguard the APS from systemic risk .